Community-Based Action Research Intervention to Promote Occupational Health Nursing of Portuguese Quarry Workers - Catarina Magalhães Alves; Carminda Morais; Filipe Alves; Diogo Magalhães; Guilherme Gonçalves; Irma Brito (MDPI AG, 2024)
The northern region of Portugal has the largest number of companies manufacturing granite and stone products, which has become the region's trademark. In the municipalities of Marco de Canaveses and Penafiel, the economic activity of this area is important. However, the lack of attractiveness of this activity, combined with the high prevalence of silicosis and tuberculosis in this population, has led to a growing shortage of labor. In order for this project to be the result of collaborative, integral work centered on the people who are the target of health promotion, we used the Participatory Health Research (PHR) approach, based on the PRECEDE-PROCEED model, to implement a mixed-methods study, including participant observation, interviews and document analysis. These data were used to co-create a study design. In 2021, a total of 102 interviews were carried out and self-completion surveys were distributed: the Fantastic Lifestyle Questionnaire (FLQ) and the EQ-5D-3L. Within the scope of occupational health nursing and in the field of action of public health nurses, with the interviews and self-completed surveys carried out, we identified potential focuses for occupational health nursing intervention to promote the health of stone industry workers: adherence to protective measures, energy balance deficit, tobacco and alcohol consumption and access to health services. Data analysis made it possible to assess the prevalence of risk behaviors by order and to involve managers and workers in the co-creation of a health promotion program. The accurate identification of the focuses for nursing intervention not only improves the effectiveness of occupational health services, allowing for targeted interventions adapted to workers' needs, but also contributes considerably to health promotion in the workplace, resulting in safer working environments, a reduction in occupational diseases and, consequently, a healthier and more productive workforce. This protocol of this study was not registered.